2018
DOI: 10.1159/000493230
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43: a New Therapeutic Target Against Chronic Kidney Disease

Abstract: Chronic kidney disease is an incurable to date pathology with a continuously growing incidence that contributes to the increase of the number of deaths worldwide. With currently no efficient prognostic or therapeutic options being available, the only possibility for treatment of end-stage renal disease is renal replacement therapy through dialysis or transplantation. Understanding the molecular mechanisms participating in the progression of renal diseases and uncovering the pathways implicated will permit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 84 publications
0
36
0
2
Order By: Relevance
“…Consequently, they postulated that this change in Cx43 was altered by the development of inflammation in the damaged kidney [36]. Therefore, Cx43 is considered a new mediator of renal disease involved in central processes of inflammation and fibrosis, while its inhibition even after the initiation of the disease attenuates renal damage and preserves renal function in animal models of vascular, tubular, and glomerular CKD [48]. Although renal tissue expresses several Cxs, only a few studies have described the involvement of GJs and HCs in kidney damage, and no signaling pathway has been clearly associated with these changes [36,41,42].…”
Section: Connexins In Hypertensive Nephropathymentioning
confidence: 99%
“…Consequently, they postulated that this change in Cx43 was altered by the development of inflammation in the damaged kidney [36]. Therefore, Cx43 is considered a new mediator of renal disease involved in central processes of inflammation and fibrosis, while its inhibition even after the initiation of the disease attenuates renal damage and preserves renal function in animal models of vascular, tubular, and glomerular CKD [48]. Although renal tissue expresses several Cxs, only a few studies have described the involvement of GJs and HCs in kidney damage, and no signaling pathway has been clearly associated with these changes [36,41,42].…”
Section: Connexins In Hypertensive Nephropathymentioning
confidence: 99%
“…In recent years, trans-membrane proteins called connexins have attracted considerable interest as a potential future target for treatment of multiple disease states [5][6][7][8], including various forms of CKD [9]. Connexins assemble into hexameric structures called hemichannels, forming pores in the membrane which directly link the cytoplasm of adjacent cells through the formation of gap junctions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia and downstream changes in connexin expression are critical in the development and progression of secondary micro-vascular complications, [12][13][14][15] with glucose decreasing gap junction conductance and disrupting cellular homeostasis in a variety of cell types [16][17][18][19]. Evidence that connexin expression is linked to renal damage in CKD [9,11,12,[20][21][22][23][24], suggests that they represent a viable therapeutic target for treatment of the disease. Recent studies have confirmed elevated levels of predominant isoform Cx43, in human and rodent models of early renal disease [20,21] whilst the Cx43 +/− unilateral ureteral obstruction (UUO) mouse demonstrates reduced collagen deposition and macrophage infiltration [24].…”
Section: Introductionmentioning
confidence: 99%
“…Cx43 is perceived to be the most broadly expressed connexin in humans. Extensive studies involving Cx43 have indicated that aside from its role in communication, it can also regulate gene transcription, properties of the cytoskeleton, ATP transport, cell stress, and damage [23]. As an example of its abundance, Cx43 is widely expressed in the heart and is critical for myocyte growth and function.…”
Section: Introductionmentioning
confidence: 99%